Nonpathogenic Escherichia coli Can Contribute to the Production of Shiga Toxin - Gamage, Shantini D. (American Society for Microbiology, 2003)
The food-borne pathogen, Escherichia coli O157:H7, has been associated with gastrointestinal disease and the life-threatening sequela hemolytic uremic syndrome. The genes for the virulence factor, Shiga toxin 2 (Stx2), in E. coli O157:H7 are encoded on a temperate bacteriophage under the regulation of the late gene promoter. Induction of the phage lytic cycle is required for toxin synthesis and release. We investigated the hypothesis that nonpathogenic E. coli could amplify Stx2 production if infected with the toxin-encoding phage. Toxin-encoding phage were incubated with E. coli that were either susceptible or resistant to the phage. The addition of phage to phage-susceptible bacteria resulted in up to 40-fold more toxin than a pure culture of lysogens, whereas the addition of phage to phage-resistant bacteria resulted in significantly reduced levels of toxin. Intestinal E. coli isolates incubated with Shiga toxin-encoding phage produced variable amounts of toxin. Of 37 isolates, 3 produced significantly more toxin than was present in the inoculum, and 1 fecal isolate appeared to inactivate the toxin. Toxin production in the intestine was assessed in a murine model. Fecal toxin recovery was significantly reduced when phage-resistant E. coli was present. These results suggest that the susceptibility of the intestinal flora to the Shiga toxin phage could exert either a protective or an antagonistic influence on the severity of disease by pathogens with phage-encoded Shiga toxin. Toxin production by intestinal flora may represent a novel strategy of pathogenesis.